Genomics and transcriptomics in veterinary oncology - Harrison, Bridget Marie (Oncol Lett, 2021)
The sequencing of the canine genome, combined with additional genomic technologies, has created opportunities for research linking veterinary genomics with naturally occurring cancer in dogs. Also, as numerous canine cancers have features in common with human cancers, comparative studies can be performed to evaluate the use of cancers in dogs as models for human cancer. There have been several reviews of veterinary genomics but, to the best of our knowledge, there has been no comprehensive review of the literature of canine cancer genomics. PubMed and CAB Abstracts databases were searched to retrieve relevant literature using the search terms ‘veterinary’, ‘cancer’ or ‘oncology’, and ‘genomics’ or ‘transcriptomics’. Results were manually assessed and grouped based on the techniques used, the cancer type investigated and genomic lesions targeted. The search resulted in the retrieval of 44 genomic and transcriptomic studies, with the most common technique employed being comparative genomic hybridization. Across both fields, the most commonly studied cancer type was canine osteosarcoma. Genomic and transcriptomic aberrations in canine cancer often reflected those reported in the corresponding human cancers. Analysis of the literature indicated that employing genomic and transcriptomic technologies has been instrumental in developing the understanding of the origin, development and pathogenesis of several canine cancers. However, their use in canine oncology is at an early phase, and there appears to be comparatively little understanding of certain canine cancer types in contrast to their human forms. Aberrations detected in all tumors were tabulated, and the results for osteosarcoma, lymphoma and leukemia, mast cell tumor, transmissible venereal tumor and urothelial carcinoma discussed in detail.